A Bibliometric Analysis of Complex Problem-Solving Approaches in Engineering Education - Azizan, Mohd Fikri; Mohd Matore, Mohd Effendi Ewan; Omar, Marlissa (Journal of Applied Science, Engineering, Technology, and Education, 2025)
The evolving landscape of engineering education requires the development of advanced cognitive skills, particularly complex problem-solving (CPS). As engineering challenges grow in complexity, CPS has become a vital competency. However, research on CPS in engineering education remains scattered. This study presents a systematic bibliometric analysis to uncover trends, key contributors, and thematic focuses in CPS-related research. Using the Scopus database and VOSviewer 1.6.20, the study analyzed publications based on co-authorship, co-citation, and keyword co-occurrence. The five-stage bibliometric approach by Masitoh et al. (2021) and Bukar et al. (2023) was adopted, encompassing keyword selection, data retrieval, screening, analysis, and visualization. Findings show a notable rise in CPS publications after 2010, peaking between 2022 and 2024. Dominant keywords include “active learning,” “simulation,” “artificial intelligence,” and “project-based learning,” indicating a shift toward AI-driven, technology-enhanced approaches. China, the United States, and India lead in research output, reflecting global efforts in reforming engineering education. The study highlights the growing emphasis on interdisciplinary and problem-based learning. Despite this momentum, regional disparities remain. Insights from this analysis are valuable for curriculum developers, educators, and policymakers to enhance CPS integration and guide future research toward more holistic and inclusive approaches